How Blockchain interrelates with trust in the supply chain context: Insights from tracing sustainability in the metal industry - Abbas Batwa; Andreas Norrman; Ala Arvidsson (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: Blockchain technology (BCT) is argued to deliver a trustless system where trust is driven by technology rather than individuals or organizations. This paper studies this claim using insights related to tracing sustainability features in the metal industry. Methodology: The results of this study are based on multiple case studies of two supply chains (steel and copper) piloting a traceability solution for tracing metal sustainability throughout the supply chain. The data are collected and analyzed from multiple actors using sources such as interviews and secondary documents. Findings: The study empirically supported that even if the BCT is applied, there will be a need for: benevolence, integrity, ability, and credibility dimensions of trust. Hence, a trustless system is still not yet applicable. Moreover, to remove the need for the trusted third party certificates, there are boundary conditions such as governance structures and standardizations that must be addressed first. Originality: The concept of trust in the novel phenomena of the BCT was investigated from different point of views, such as the supplier and the buyer views. Moreover, different contexts were examined such as the commercial and the sustainability contexts. Therefore, this paper is among the first to handle the issue of trust from these regards.
urn:nbn:de:gbv:830-882.0161679; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Artificial Intelligence; Blockchain